Un-blogged : a fencer's ramblings - Walker, Henry; Farrell, Keith (Brisbane, Queensland : Sword and Book Enterprises, 2019)
'A Fencer's Ramblings' is a blog by Henry Walker which he started in May 2010 to spread knowledge about the subject of Historical European Martial Arts, and indeed fencing in general. Whithin the pages of this book you will find a selection of articles from the blog, along with bonus extra articles of interest by the author. These have been recently updated for this book, with a view to retaining their original purpose: to inform and educate the reader about various elements on the subject of fencing. Some articles are conversational, others are written from a more academic point of view. The subject areas are wide and the material is varied; thoughts will be provoked and challenged. This book is a treasure-trove of information conveniently brought together in one place, for all readers with a love of swords and swordplay.
Includes bibliographical references.
Keywords: Swordplay; Fencing; Swordsmen; Martial arts -- Europe -- History